Evaluation Program of the Futsal Coaching at the Futsal Association of Central Java Province - Muhsin, Muhamad; Hartono, Mugiyo; Setyawati, Heny (Journal of Physical Education and Sports, 2021)
Central Java's Futsal Association of Province (AFP) cannot develop independently. Inadequate development of sustainable sports achievement is contrary to the achievement demands that will succeed. This research evaluates aspects of the organization, funding, human resources, infrastructure, and training programs in developing AFP in Central Java Province. Research used Strake states that evaluation is divided into 3, namely: 1) preparation/preliminaries (antecedents),2) processes/transactions (transaction processes), 3) results (outcomes). The Countenance Stake research model consisted of two matrices: description and consideration. The description category consisted of plans (intent) and observation. The consideration category consisted of standards and considerations. The research result was the Antecedent (Context) Football Association of Indonesia (PSSI) as a unique forum for futsal was the future root of Indonesian futsal. The infrastructure's significance in helping the smooth running of the trainer program could achieve the target. The feasibility of the infrastructure also supports it. The welfare of athletes and coaches needed to be the management's concern. Conclusion the team's achievements were intervention, attention from AFP management, programs, coaching, infrastructure, good relationship communication between coaches and athletes. The conclusion is that the evaluation of the futsal coaching program in Central Java seen from the three factors is good and can compete for achievements.